Penerapan Konseling Kelompok dengan Teknik Assertive Adaptive untuk Mengatasi Penyesuaian Diri - Azizah Pebrianti; Abdur Razzaq; Lena Marianti (Scidacplus, 2024)
Basically, adjustment involves individuals and their environment, this is also the case with inmates, this is because inmates who have just entered are required to be able to adapt to environmental conditions, individuals, and the rules that apply in prison. According to Picken, new inmates experience higher levels of stress. Therefore, to help solve adjustment problems for inmates in prison, researchers applied assertive adaptive techniques with group counseling services. Therefore, the researcher chose the title